Analisis ABC Dalam Perencanaan Pengadaan Perbekalan Farmasi di Puskesmas Gamping 1 Yogyakarta - Zulpadly, Fiqri; Rahayu, Siti Nurhaliza Nadya (Jurnal Farmasi Udayana; Vol. 12, No 1, Tahun 2023DO - 10.24843/JFU.2023.v12.i01.p07, 2023)
In carrying out the task of managing drugs and medical consumables, Primary Health Center has the responsibility to create a management that is done effectively and efficiently. One of them is managing a pharmaceutical inventory. In this study, ABC analysis on the planning of drugs and medical consumables procurement at Yogyakarta Gamping I Public Health Center was carried out with the aim of finding out the ABC grouping of its inventory based on its investment value and also the percentage proportion of each group. This research is a non-experimental study with descriptive analysis using quantitative data which was conducted retrospectively. Primary data was obtained through an interview with the pharmacist in charge at Yogyakarta Gamping I Primary Health Center. The source of the secondary data is the facility’s history of the procurement of drugs and medical consumables based on LPLPO from the period of Januari-Desember 2021. Results showed that among 137 items of drugs, only 0,73% of them were included in group A. Group B consists of 9 items and group C has 127 items. For medical consumables, 16,67% of the 54 items were categorized into group A. Group B has the percentage of 22,22% of items and group C with the remaining 61,11%. Keywords: abc analysis, procurement planning